The Effect of Voluntary Disclosure of Information on the Quality of Information, Decision-Making and Shareholder Behavior - Javad Rezazadeh; Mohammad Javad Tasaddi Kari; Rouhollah Kheiri (Environmental Energy and Economic Research)
According to the information content of financial reports, this research aims to investigate the effect of Voluntary Disclosure (VD) on the quality of information, the quality of decision and the behavior of shareholders. The population of the research is the firms listed in Tehran Stock Exchange. Based on the screening, 138 firms were selected between 2013 and 2021. The required data was extracted through the website of the stock exchange organization. The collected data were analyzed through econometric models and EViews software. According to the results, there is a significant relationship between VD, disclosure quality, decision quality and shareholders' behavior. Therefore, the amount of stock transactions can be a function of the amount of disclosure characteristics and the quality of the decision. By focusing on the shareholders, the results can provide a basis for making managers' decisions to meet their information needs and improve the transparency of the financial market.